Time constant for the dermal absorption of semivolatile organic compounds from the gas phase of indoor air. (December 2019) - Simon, Laurent
Highlights: A time constant was computed for the absorption of semivolatile organic compounds. Tools were developed to facilitate more effective risk assessment strategies. The total mass of organic compounds absorbed depends on the exposure time. Abstract: A Laplace transform-based technique was applied to solve a mechanistic model and simulate scenarios often encountered in the percutaneous absorption studies of semivolatile organic compounds (SVOCs) from indoor air. The system included the stratum corneum layer, a skin surface lipid region and the viable epidermis. The new framework made it possible to provide analytical expressions for the effective time constant ( t eff ). This dynamic key performance indicator helped estimate the time required to reach either a steady-state absorption rate or the total amount of SVOC absorbed into the bloodstream. In the case of a constant concentration C g of the chemical, the flux reached 98.1% of its steady-state value at 4 t eff . When participants were exposed to 29.4 µg/cm 3 of m-xylene vapors during an 8-hour period and zero concentration thereafter, the mass of m-xylene entering the bloodstream and the time constant were 4.40 mg and 1.02 h, respectively. The mass transfer coefficient between the air and the surface of the lipid layer ( h m ) remained unchanged. The methodology calculated t eff in cases of varying h m and temporary C g when an SVOC was absorbed into the capillaries after a relatively short exposure time.